Role of locomotor efference copy in vertebrate gaze stabilization - Straka, Hans; Lambert, François M.; Simmers, John (Frontiers in Neural Circuits, 2022)
Vertebrate locomotion presents a major challenge for maintaining visual acuity due to head movements resulting from the intimate biomechanical coupling with the propulsive musculoskeletal system. Retinal image stabilization has been traditionally ascribed to the transformation of motion-related sensory feedback into counteracting ocular motor commands. However, during locomotion in the amphibian Xenopus laevis, efference copies (ECs) of the spinal motor program that generates axial- or limb-based propulsion directly elicit compensatory eye movements. The spatio-temporal specificity of this intrinsic feed-forward mechanism has been extensively explored in semi-intact and isolated brain/spinal cord preparations. During fictive locomotion in larvae, ascending ECs from rostral spinal central pattern generating (CPG) circuitry are relayed through a defined ascending pathway to the mid- and hindbrain ocular motor nuclei to produce conjugate eye rotations during tail-based undulatory swimming in the intact animal. In post-metamorphic adult frogs, this spinal rhythmic command switches to a bilaterally-synchronous burst pattern that is appropriate for generating convergent eye movements required for maintaining image stability during limb kick-based rectilinear forward propulsion. The transition between these two fundamentally different coupling patterns is underpinned by the emergence of altered trajectories in spino-ocular motor coupling pathways that occur gradually during metamorphosis, providing a goal-specific, morpho-functional plasticity that ensures retinal image stability irrespective of locomotor mode. Although the functional impact of predictive ECs produced by the locomotory CPG matches the spatio-temporal specificity of reactive sensory-motor responses, rather than contributing additively to image stabilization, horizontal vestibulo-ocular reflexes (VORs) are selectively suppressed during intense locomotor CPG activity. This is achieved at least in part by an EC-mediated attenuation of mechano-electrical encoding at the vestibular sensory periphery. Thus, locomotor ECs and their potential suppressive impact on vestibular sensory-motor processing, both of which have now been reported in other vertebrates including humans, appear to play an important role in the maintenance of stable vision during active body displacements.